1100 C-Reactive Protein Concentrations in Neonates with Hypoxic-Ischaemic Encephalopathy and Effect of Total Body Hypothermia. (October 2012) - Sanka, S; Muniraman, H; Gardner, D; Pawaletz, A; Jennings, C; Vayalakkad, A; Victor, S; Turner, MA; Clarke, P
Abstract : Background and Aims: Production of C-reactive protein (CRP), an acute phase reactant of hepatic origin, may be affected by perinatal asphyxia. This study tested hypotheses that circulatory CRP concentrations correlate with clinical severity of hypoxic-ischaemic encephalopathy (HIE) and that total body hypothermia modulates CRP response. Methods: Clinical records in three centres were reviewed for neonates ≥36 weeks' gestation admitted between 01/07/06 and 30/06/11 with HIE of any severity (grades 1–3 Sarnat-Sarnat). Participating centres adopted routine cooling at different dates. Data extracted included CRP concentrations in the first postnatal week measured during routine clinical practice, clinical HIE grading, and reception of therapeutic hypothermia. Proportions with raised CRP (>10 mg/L), and maximum CRP concentrations were assessed according to HIE grade and whether cooled. Results: A raised CRP was present in 150/259(58%) neonates during the first postnatal week (HIE1: 30/73[41%], HIE2: 83/129[64%], HIE3: 37/57[65%], p=0.003) but elevated maximum concentrations (peaking median day 3) did not differ between HIE grades (median [range] HIE1: 31.3 [10.0–188.1] mg/L, HIE2: 32.5 [10.0–305.9] mg/L, HIE3: 34.0 [10.2–346.5] mg/L, p=0.48). A raised CRP was present in 117/187(63%) cooled and 33/72(46%) non-cooled infants (p=0.02), but their peak CRP concentrations did not differ (median [range] CRP cooled vs. non-cooled: 31.9 [10.0–346.5] mg/L vs. 53.0 [10.4–188.1] mg/L, p=0.26). Conclusion: A raised CRP is a common finding in the first postnatal week in neonates admitted with HIE and is found in most infants with moderate-severe HIE. Peak CRP concentrations did not differ with clinical HIE grade and whole body hypothermia did not significantly affect peak CRP concentrations.